Vitamin D Deficiency and its Correlation with the Severity of Heart Disease in Dilated Cardiomyopathy Patients - Gaur, Kuldeep Kumar; Ghotekar, LH; Margekar, Shubha Laxmi; Kumar, Tarun; Singh, Ritu (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: Cardiomyopathy is primarily a disorder of the cardiac muscle that causes myocardial dysfunction and is not the result of disease or dysfunction of other cardiac structures, systemic arterial hypertension and valvular stenosis or regurgitation. Aim: The present study aimed to determine the prevalence of vitamin D deficiency and its correlation with the severity of heart disease in patients with dilated cardiomyopathy (DCMP). Method: 70 ECHO-proven DCMP cases were enrolled from the medicine/ cardiology department of LHMC & associated hospitals and ABVIMS & Dr. RML Hospital, New Delhi from November 2019 to October 2021. DCMP patients with ages more than 18 years who were willing to give consent and does not meet any of the exclusion criteria were enrolled in this study. Results: Mean age of idiopathic DCMP patients was 48.3 ± 15.2. There were more males 48 (69%) than females 22 (31%). The mean ejection fraction was 26.6 ± 7.3, while the mean fractional shortening was 17.6 ± 3.1. Vitamin D deficiency was observed in 90% of patients, among which 68.5% were having moderate vitamin D deficiency and 10% were having severe vitamin D deficiency. Conclusion: In our study, vitamin D levels were inversely correlated with the severity of heart disease in DCMP patients.